Effect of Brand Attributes on the Customer’s Wish to Pay Premium with Mediating Input of Attitudinal Loyalty in Pakistan - Sameed Altaf; Raheel Farooqi; Muhammad Sufyan Ramish PhD; Reema Frooghi PhD; Syed Rizwan Ali (Al-Qanṭara, 2025)
The study performed to empirically investigate the correlation between brand management practices and customers' wish to pay in Pakistan to bring up with enhanced strategic positioning, fostering of deeper customer loyalty, and drive higher premiums among customer. The study focused on primary data with the application of the survey-based approach to collect the required set of information using questionnaire as data collection tool. The study collected with the 384 response and applied it with the structural equation model using PLS Smart as the software to perform with the data run and extract the outcomes for the hypotheses testing. The results of the study revealed that there is a significant and positive effect of attitudinal loyalty on customer's wish to pay premium with consideration figure of 0.000 and having coefficient figure of 0.76 hence considerable at 5 percent level of consideration. There is also a considerable and positive effect of brand love on attitudinal loyalty with consideration figure of 0.12 and having coefficient figure of 0.016 hence considerable at 5 percent level of consideration. There is also a considerable and positive effect of brand attachment on attitudinal loyalty with consideration figure of 0.000 and having coefficient figure of 0.28 hence considerable at 5 percent level of consideration. The faced time as a major constraint while the study revealed with the considerable effect of brand attributes on the customer’s wish to pay premium with intermediary part of attitudinal loyalty in Pakistan.